Pemanfaatan Model Pembelajaran Edutainment dalam Pemerolehan Bahasa Indonesia pada Anak Usia Dini - Wisnu Kristanto; Nur Aini Saura Putri; Alfina Citra Sukmawati (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Introducing the Indonesian language to early childhood learners involves building conceptual understanding and vocabulary through active participation and meaningful use in everyday life. Language acquisition in early childhood also requires learning experiences that are meaningful, enjoyable, and contextual. This learning model integrates educational and entertainment elements, enabling children to acquire language naturally through play activities, singing, storytelling, and social interaction. This study aims to describe early childhood Indonesian language acquisition through the implementation of an edutainment learning model. The study employs a descriptive research approach with early childhood learners in PAUD (Early Childhood Education) institutions as the subjects. Data were collected through observation, field notes, and documentation of learning activities. The results indicate that edutainment-based learning facilitates vocabulary acquisition, increases children’s confidence in oral language use, and helps them understand the meaning of utterances in everyday contexts. The findings reveal that a needs analysis shows existing Indonesian language instruction lacks a systematic instructional design and adequate digital teaching materials, highlighting the need for a model that integrates entertainment-based learning and digital applications. Expert validation confirms that the edutainment learning model is appropriate for introducing Indonesian to early childhood learners in kindergarten settings. The implementation of the edutainment model has proven effective in increasing early learners’ exposure to and use of the Indonesian language. The developed edutainment learning model, supported by digital learning applications, provides a practical reference for teachers, parents, and early childhood institutions in creating engaging, meaningful, and effective Indonesian language learning experiences.